The woman -reason for study and inspiration in constant transformation - Llanos Bustamante, Eduardo (2021)
The present essay is a reflection on women as a subject for study, but also as an inspiration both in psychoanalytic disciplines and in fine arts in the light of the constant vicissitudes and profound transformations that we are going through constantly and today more than ever. These are two entry ways to the subject in search of complementarity and mutual inspiration without neglecting  the peculiarities of a country like ours in the middle of the bicentennial and the burden of a global pandemic.